2009
DOI: 10.1002/msc.152
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of the sexual health of women with rheumatoid arthritis

Abstract: Sexual health problems are common for women with Rheumatoid Arthritis, RA. Sexual health is covered in the International Classification of Functioning, Disability and Health (ICF) by two different fields: sexual function and intimate relationships, which are included in the ICF core sets for RA. Most patients with RA are female, and there are differences concerning sexual health between women and men with RA.The aim of this study was to explore the literature concerning the effects of RA on the sexual health o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
(56 reference statements)
2
32
1
3
Order By: Relevance
“…A total of 47 papers described the use of ICF in the contexts of a specific health condition, the most frequent being stroke [439,469,470,472,473], multiple sclerosis [444,464,465,467,477], rheumatoid arthritis [440,443,449,454,474], traumatic brain injury [455,457,459] and HIV/AIDS [441,446,447].…”
Section: Clinical Contextsmentioning
confidence: 99%
“…A total of 47 papers described the use of ICF in the contexts of a specific health condition, the most frequent being stroke [439,469,470,472,473], multiple sclerosis [444,464,465,467,477], rheumatoid arthritis [440,443,449,454,474], traumatic brain injury [455,457,459] and HIV/AIDS [441,446,447].…”
Section: Clinical Contextsmentioning
confidence: 99%
“…However, health care providers often lack education concerning sexological issues, and their attitudes towards working to promote sexual health can be challenged by their own believed non-importance of sexual health for persons with disease or disability (Esmail, Darry, Walter, & Knupp, 2010;Low & Zubir, 2000). Sexual health is strongly related to feelings of well-being and general health (Field et al, 2013;Lindau & Gavrilova, 2010;Ratner, Erekson, Minkin, & Foran-Tuller, 2011), and previous research has shown that rehabilitation can promote sexual health (Kristina Areskoug- Josefsson & Gard, 2015;K. Areskoug-Josefsson & Oberg, 2009;Egan et al, 2013;Josefsson & Gard, 2012;Rosenbaum, 2006).…”
mentioning
confidence: 99%
“…In contrast to our country, this rate was reported higher in studies from different countries. For instance, the rate of sexual dysfunction among women with RA was reported to be 45.7% by El Miedany et al, 11 and Josefson et al 10 found a rate between 36-70%. The sexual satisfaction of couples might be influenced by social and personal factors, and expectancies on sexuality might vary across cultures.…”
Section: Discussionmentioning
confidence: 96%
“…Limitations in hand movements may limit the caressing of the partner, and limitations of bigger joints may negatively affect potential sexual intercourse positions. 9 Areskoug-Josefsson et al 10 reported that the physical, psychological and emotional effects of RA might lead to sexual problems which further affect the close relations of the patients. El Miedany et al 11 showed that 45.7% of the female patients with RA have a sexual dysfunction disorder (SDD), and secondary Sjögren syndrome, pain score, cardiovascular disorders, hip involvement, disease activity and the number of tender joints are associated with SDD.…”
mentioning
confidence: 99%